Analysis of Insulin Sensitivity Stochastic Models between STAR Original and Malaysian Cohorts - Wai Lee J.W.; Chiew Y.S.; Tan C.P.; Razak A.A.; Abdul Razak N.N. (Elsevier B.V., 2023)
Decision support systems; Glucose; Hospital data processing; Intensive care units; Physiological models; Stars; Stochastic control systems; Stochastic models; Stochastic systems; Clinical variable; Control of physiological; Control protocols; Decision supports; Glycemic control; Insulin sensitivity; Malaysians; Model-based OPC; Stochastic control; Stochastic-modeling; Insulin